Formulasi dan Uji Stabilitas Fisik Sediaan Bedak Tabur Ekstrak Etanol Daun Ciplukan (Physalis angulata L.) Sebagai Anti Fungi di Desa Tammatto Kabupaten Bulukumba - Sulfiyana H. Ambo Lau; Herman Herman (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Ciplukan (Physalis angulata L.) is a seasonal herbaceous plant from the Solanaceae family which has many benefits, one of which is as an antifungal. Research has been carried out on the formulation and physical stability test of the ethanol extract of the leaves of Ciplukan (Physalis angulata L.) as anti-fungi. The goal is to find out that ciplukan leaves contain chemical substances that can inhibit the growth of fungi on the skin and can be formulated into powder preparations. This research is a laboratory experimental research. This research includes identification tests for alkaloids, flavonoids, saponins, steroids, and tannins. The powder formulations were FI (without extract), FII (extract 10%), and FIII (extract 20%). The stability test of the preparation includes the organoleptic test, homogeneity, fine degree, pH, adhesion, and hedonic test. The results of the research identified positive compounds containing alkaloids, flavonoids, saponins, and tannins. In the stability test, all formulations showed the results according to the literature, the hedonic test was not irritating and formula FII was preferred. The conclusion is that the ethanol extract of ciplukan leaves contains antifungal compounds and can be formulated into powder with good stability